Strategies to Enhance Supervision and Control of Freight Transport in Over Dimension Over Loading (ODOL) - Suntoro , Wahyu; Maemunah , Siti; Sari , Mustika; Subastian, Djamal; Ilham, Ilham (Yayasan Sinergi Kawula Muda, 2026)
This study examines supervision strategies for freight transport at the Balonggandu and Losarang Motor Vehicle Weighing Implementation Units (UPPKB) to address the Over Dimension Over Loading (ODOL) phenomenon, which threatens national road safety and infrastructure. The primary problem analysed is the gap between the high volume of freight vehicles and the limited capacity of manual supervision, leading to logistics inefficiencies. The study employed a mixed-method descriptive approach with data collection through field observations, questionnaires administered to 100 drivers, and in-depth interviews with key informants from the Ministry of Transportation. Data were analysed using SWOT matrices and AHP weighting. The novelty of this research lies in formulating priority strategies that integrate technical operational constraints analysis with inter-agency digital enforcement design for two specific UPPKB sites using a hybrid SWOT and AHP approach. Empirical findings indicate that external opportunity factors, specifically technological support, hold the highest weight (0.490). The strategy of inter-agency integration based on Information Technology (IT) was selected as the top priority (0.113) to overcome the limitations of manual supervision, representing a priority ranking for implementation focus rather than an absolute measure of effect size. The study concludes that a transformation towards integrated digital supervision is a strategic priority, with policy implications requiring the implementation of automated sanctions and the expansion of legal liability to cargo owners to achieve national logistics efficiency.